Prevalence and characteristics of thelarche variant - Burlo, Francesca; Lorenzon, Beatrice; Tamaro, Gianluca; Fabretto, Antonella; Buonomo, Francesca; Peinkhofer, Martina; Vidonis, Viviana; Vittori, Giada; Faleschini, Elena; Barbi, Egidio; Tornese, Gianluca (Frontiers in Endocrinology, 2023)
Introduction: Girls with early thelarche may show an intermediate clinical picture between isolated premature thelarche (PT) and central precocious puberty (CPP), defined as ‘thelarche variant’ (TV), characterized by an FSH-predominant response, although a univocal definition is lacking. Methods: Retrospective analysis on 91 girls with early thelarche (<8 years) and advanced bone age and/or accelerated growth who underwent 104 LHRH tests. Patients were classified into CPP (LH peak ≥5 IU/L; n=28, 31%), TV (FSH peak ≥20 IU/L, LH peak <5 IU/L; n=15, 16%), or PT (FSH peak <20 IU/L and LH peak <5 IU/L; n=48, 53%). Results: TV patients were younger (5.51 years) and with less advanced bone age (+0.8 years). They had higher basal and peak FSH (2.5 and 26.6 IU/L) and lower basal and peak LH/FSH ratios (0.08 and 0.11). The prevalence of presence of ovarian follicles >5 mm in TV (42%) was similar to CPP but significantly higher than PT, while maximum ovarian volume was smaller in TV (1.0 cm3). At last follow-up visit (available in 60% of the cases), 44% of TV developed CPP compared to 14% of PT (p=0.04). At first evaluation, those who progressed to CPP had a higher basal FSH (3.2 IU/L), lower LH/FSH ratio (0.07) and a higher peak LH (4.1 IU/L) compared to those who did not progress to CPP (basal FSH 1.9 IU/L, p<0.01; basal LH/FSH ratio 0.12, p<0.01; peak LH 2.8 IU/L, p=0.02). Conclusion: Using laboratory parameters only as a definition, we identified the clinical, laboratory, and imaging features of TV: these girls showed less advanced bone age and FSH predominance also at baseline, with smaller ovaries but with follicles >5 mm. Almost half of girls initially diagnosed as TV developed CPP at last follow-up visit, and these girls had higher baseline FSH, lower baseline LH/FSH ratio and higher peak LH at first evaluation. Therefore, TV may represent a “precocious pre-puberty” in which the FSH predominance may initially limit the progression into proper puberty, but it may eventually trigger full puberty (even CPP, depending on the girls’ age).